Pengembangan Pendidikan Agama Islam di Desa Megulung Kidul - Mugiarto, Mugiarto (Abdibaraya, 2024)
The advancement of Islamic religious education in Megulung Kidul Village represents a key strategy to enhance both the understanding and application of Islamic principles within the local community. This research seeks to examine the process, challenges, and outcomes associated with the development of Islamic education in this area. Various initiatives are integral to this development, such as reinforcing the mosque's role as a hub for learning, elevating the quality of madrasah teachers, and holding regular religious events. The challenges encountered include limited resources, insufficient support from external entities, and a lack of engagement from the youth. Despite these obstacles, the initiative has positively influenced the community, as evidenced by increased religious comprehension, improved moral standards, and stronger social cohesion within the village. The research suggests that enhanced backing from governmental bodies and religious organizations is essential for bolstering Islamic education programs in rural settings.